Primary renal lymphoma: A clinical and radiological study - Dimopoulos, M.A.; Moulopoulos, L.A.; Costantinides, C.; Deliveliotis, C.; Pantazopoulos, D.; Dimopoulos, C. (Journal of Urology, 1996)
Purpose: We assessed the incidence, clinical and radiological features, and prognosis of patients with renal lymphoma. Materials and Methods: We studied 210 patients with symptoms, signs and radiological findings suggestive of renal cell carcinoma. Results: Final diagnosis in 6 of 210 patients (3%) was primary renal lymphoma. Radiological features were similar to those of renal cell carcinoma. Five of the 6 patients had an International Prognostic Index score of greater than 1. Despite appropriate chemotherapy, only 2 patients remain with complete remission. Conclusions: Primary renal lymphoma is unusual but not rare. The relatively poor prognosis in our patients could be attributed to the adverse prognostic factors associated with aggressive nodal lymphomas.
Keywords: kidney neoplasms; Lymphoma